(3GdMVGQI GdBThQjI (B/s - (3GdeGLOj, NRYds 1951- ((3HjQhJ(B:s (3HZOGO(B:s (3GdchjJ(B:s (3OGQ GdQGaOjf,s (3efThQGJ Jchjf ddfTQ hGdJhRjY,s, 2021)
(3GdMVGQI GdBThQjI hGMOI ef CYXe MVGQGJ GdJGQjN GdbOje, hfcGO fbhd EfgG GdCYXe Mjf jchf GdMOjK Yf MVGQI EeHQGWhQjI(B. (3dcfgG, JMJ JVNje MLI JhSYgG GdTGSY hbShJgG GdeaQWI, fGdJgG SgGe GdfbO heYGhd GdJgOje aThghgG, Ke fGdgG GdEgeGd hGdJgejT, HYO Cf bVJ YdjgG JMGdaGJ eQjHI, hLGA Pdc GdEgeGd hGdfSjGf, aj GdeGVj hGdMGVQ, ebUhOG hMGhdhG ZeW efLRGJgG hYXeJgG GdJj cGfJ CYdi ef GdLejY PGJ jhe(B. (3jQi GdcJGH Cf gPg GdMVGQI JYQVJ deDGeQI EbdjejI HTYI bGeJ HESbGWgG, Ke OafgG hbJd TYHgG Ch JgLjQg hCSQg hJTQjOg hWeQ eOfg JMJ GdJQGH, hfgH efLRGJg GdMVGQjI hEMGdJgG ddOhd hGdTYhH GdeJBeQI YdjgG BfPGc(B. (3hbO GSJKeQJ gPg GdeDGeQI GdHQhHGZGfOG GdSdHjI GdTGFYI VO LHQhJ hWZjGf GdEeHQGWhQjI GdBThQjI ef CLd GdJSJQ Ydi LQjeI GdEHGOI hGdfgH GdJj eGQSJgG gj VOgG(B. (3Mjf hUa (B((3gGQj SGZR(B) (3GdMVGQI GdBThQjI H (B((3GdYXeI Edi CbUGgG(B)(3, abO cGf jTjQ, HhVhM, Edi beI YXjeI ef bee MVGQGJ hGOj GdQGaOjf hGdTQb GdCOfi GdbOje hGdYGde GdbOje cdg(B. (3agj GdMVGQI GdJj GLJeYJ ajgG NdGUGJ YUQgG GdPj GeJO deG jbQH ef Cdaj SfI eJhGUdI, dcfgG GSJWGYJ aj GdbQhf GdKdGKI GdCNjQI ef JGQjNgG (B((3GdYUQ GdBThQj GdMOjK(B) (3Cf JQJaY HCLfMI BThQ Edi GdCYGdj hJWjQ ahb GdHdOGf hGdMVGQGJ eLSOI, dChd eQI, aj JGQjN GdEeHQGWhQjGJ feWG EOGQjG fhYjG eMceG ef GdEeHQGWhQjGJ GdPj bdOJg cd GdEeHQGWhQjGJ HYOgG(B. (3jJfGhd GdLRA GdChd ef cJGH GdMVGQI GdBThQjI, YTQI aUhd JHOC HaUd JegjOj Yf BThQ hYde hYdeGA GdBThQjhdhLj, hJfGhd GdaUhd GdeJHbjI YfGUQ GdMVGQI GdBThQjI (B: (3GdLZQGajI hGdJGQjNjI hGdSjGSjI hGdbGfhfjI hGdYScQjI hGdeOfjI hGdGbJUGOjI hYfGUQ GddZI hGdcJGHI hGdCOH hGdacQ, hGdYfGUQ GdGLJeGYjI(B. (3Ke Jced YfGUQ GdMVGQI GdBThQjI aj GdLRA GdKGfj(B.s
(3jTJed Ydi cTGaGJ(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3JGQjNs -- (3GdYQGbs -- (3BThQs